The Kolchan: Delineation of a New Northern Athapaskan Indian Group - Hosley, Edward (ARCTIC, 1968)
Proposes that a group of inhabitants of the upper Kuskokwim River in Alaska be designated the Kolchan. They are concentrated primarily in Nikolai Village with one extended family at Telida 50 mi north. Earlier considered a division of the Ingalik (cf No. 72242), archeological and ethnographic study shows them to be an independent geographical, cultural and linguistic entity. They differ markedly from the Ingalik on the Yukon River in their social organization, which most closely resembles the Athapaskan groups to the north and east, the Tanana and Tanaina. Their linguistics are not easily classified. Following the decimation of the caribou in the 1920s, the Kolchan subsistence base has focused more on fishing, trapping and wage labor. As a group they tend to be conservative and remain one of the least acculturated groups in interior Alaska. Les Kolchan: définition d'un nouveau groupe d'Athapaskan septentrionaux. Des recherches archéologiques et ethnographiques dans la région de la haute Kuskokwim, dans l'Alaska intérieur, ont permis de définir le territoire et la culture d'un groupe Athapaskan de l'Alaska qui n'avait jamais été étudié auparavant. La reconstruction culturelle indique que les habitants de la région, considérés jusqu'ici comme un sous-groupe des Ingalik, forment une entité géographique, culturelle et linguistique indépendante.